2020
DOI: 10.1042/bst20200389
|View full text |Cite
|
Sign up to set email alerts
|

Smc5/6, an atypical SMC complex with two RING-type subunits

Abstract: The Smc5/6 complex plays essential roles in chromosome segregation and repair, by promoting disjunction of sister chromatids. The core of the complex is constituted by an heterodimer of Structural Maintenance of Chromosomes (SMC) proteins that use ATP hydrolysis to dynamically associate with and organize chromosomes. In addition, the Smc5/6 complex contains six non-SMC subunits. Remarkably, and differently to other SMC complexes, the Nse1 and Nse2 subunits contain RING-type domains typically found in E3 ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 126 publications
(171 reference statements)
0
30
0
Order By: Relevance
“…The precise cellular roles of the Smc5/6 complex remain enigmatic, but mutations within its component proteins have clear and definite impacts on DNA replication and DNA damage repair processes, in particular acting to suppress inappropriate homologous recombination structures that can be formed when replication forks stall or collapse, as well as assisting in resolution of sister chromatids during meiosis [reviewed in refs. [8][9][10][11]. Smc5/6 is also known to be a viral restriction factor for hepatitis B 12,13 , herpes simplex-1 14 and papillomavirus type 31 viruses 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The precise cellular roles of the Smc5/6 complex remain enigmatic, but mutations within its component proteins have clear and definite impacts on DNA replication and DNA damage repair processes, in particular acting to suppress inappropriate homologous recombination structures that can be formed when replication forks stall or collapse, as well as assisting in resolution of sister chromatids during meiosis [reviewed in refs. [8][9][10][11]. Smc5/6 is also known to be a viral restriction factor for hepatitis B 12,13 , herpes simplex-1 14 and papillomavirus type 31 viruses 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The precise cellular roles of the Smc5/6 complex remain enigmatic, but mutations within its component proteins have clear and definite impacts on DNA replication and DNA damage repair processes, in particular acting to suppress inappropriate homologous recombination structures that can be formed when replication forks stall or collapse, as well as assisting in resolution of sister chromatids during meiosis [reviewed in ( 8 - 11 )]. Smc5/6 is also known to be a viral restriction factor for hepatitis B ( 12 , 13 ), herpes simplex-1 ( 14 ) and papillomavirus type 31 viruses ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…More work will be required to determine structural changes in Smc5/6 during its ATPase cycle and DNA interactions. These future studies will provide further insights into the observed DNA linking and sumoylation activities of the complex (16,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 90%
“…To test the possibility that the co-evolved Nse2 and Nse5-6 have functional connections, we considered the unique sumoylation function of the Smc5/6 complex that is not shared by other SMCs (16)(17)(18)(19). Nse2 sumoylates Smc5, Smc6, and Nse4, among other substrates, and the sumoylation of Smc5 and 6 contributes to DNA replication and repair (16). However, the functional mechanisms of Nse2 as a SUMO ligase remain to be understood.…”
Section: Nse5 Sumo-interacting Motifs Affect Smc5 and 6 Sumoylationmentioning
confidence: 99%
See 1 more Smart Citation